Dose–response effects of physical activity on all-cause mortality and major cardiorenal outcomes in chronic kidney disease. (11th March 2021) - Kuo, Chou-Pin; Tsai, Ming-Tsun; Lee, Kuo-Hua; Lin, Yao-Ping; Huang, Shao-Sung; Huang, Chin-Chou; Tseng, Wei-Cheng; Tarng, Der-Cherng
Abstract: Aims: Physical activity has a protective effect against mortality and cardiovascular events in chronic kidney disease (CKD) patients. Nonetheless, how different levels of physical activity affect the health benefits in CKD remains unclear. This study aimed to investigate the dose–response effects of physical activity on mortality and major cardiorenal events in CKD. Methods and results: We evaluated a longitudinal cohort of 4508 Taiwanese CKD patients between 2004 and 2017. Physical activity was assessed by the NHANES questionnaire and quantified in metabolic equivalent-hours per week (MET-hour/week). Patients were categorized into highly active (≥7.5 MET-h/week), low-active (0.1 to <7.5 MET-h/week), or inactive (0 MET-h/week) groups. Cox regression and restricted cubic spline models were utilized to explore the association between physical activity and the risks of study outcomes, including all-cause mortality, end-stage renal disease (ESRD), and major adverse cardiovascular events (MACE, a composite of cardiovascular death, myocardial infarction, ischaemic stroke, and hospitalized heart failure). During a median follow-up of 686 days, 739 death, 1059 ESRD, and 521 MACE events occurred. Highly active group had the lowest chance of all study outcomes, followed by low-active and inactive groups ( P  <   0.001). Multivariable Cox regression showed that only highly active group was independently associated with lower risks for all-cause mortality [hazard ratio (HR) 0.62; 95% confidence interval (CI) 0.53–0.74], ESRD (HR 0.83, 95% CI 0.72–0.96), and MACE (HR 0.63, 95% CI 0.51–0.76) compared to the inactive group. The risks of MACE did not further decrease once physical activity surpassed 15 MET-h/week, indicating a U-shaped association. The results were consistent in the subgroup and sensitivity analyses. Conclusion: Physical activity of 7.5 to <15 MET-h/week is associated with lower risks of adverse cardiorenal outcomes and should be integrated into the care of CKD.